Age related differences in dynamics of specific memory B cell populations after clinical pertussis infection. - Inonge van Twillert; Jacqueline A M van Gaans-van den Brink; Martien C M Poelen; Kina Helm; Betsy Kuipers; Maarten Schipper; Claire J P Boog; Theo J M Verheij; Florens G A Versteegh; Cécile A C M van Els (PLoS ONE, 2014)
For a better understanding of the maintenance of immune mechanisms to Bordetella pertussis (Bp) in relation to age, we investigated the dynamic range of specific B cell responses in various age-groups at different time points after a laboratory confirmed pertussis infection. Blood samples were obtained in a Dutch cross sectional observational study from symptomatic pertussis cases. Lymphocyte subpopulations were phenotyped by flowcytometry before and after culture. Memory B (Bmem) cells were differentiated into IgG antibody secreting cells (ASC) by polyclonal stimulation and detected by an ELISPOT assay specific for pertussis antigens pertussis toxin (Ptx), filamentous haemagglutinin (FHA) and pertactin (Prn). Bp antigen specific IgG concentrations in plasma were determined using multiplex technology. The majority of subjects having experienced a clinical pertussis episode demonstrated high levels of both Bp specific IgG and Bmem cell levels within the first 6 weeks after diagnosis. Significantly lower levels were observed thereafter. Waning of cellular and humoral immunity to maintenance levels occurred within 9 months after antigen encounter. Age was found to determine the maximum but not base-line frequencies of Bmem cell populations; higher levels of Bmem cells specific for Ptx and FHA were reached in adults and (pre-) elderly compared to under-fours and schoolchildren in the first 6 weeks after Bp exposure, whereas not in later phases. This age effect was less obvious for specific IgG levels. Nonetheless, subjects' levels of specific Bmem cells and specific IgG were weakly correlated. This is the first study to show that both age and closeness to last Bp encounter impacts the size of Bp specific Bmem cell and plasma IgG levels.